2002
DOI: 10.1055/s-2002-23629
|View full text |Cite
|
Sign up to set email alerts
|

Sphincter of Oddi Dysfunction: Pancreaticobiliary Sphincterotomy with Pancreatic Stent Placement Has a Lower Rate of Pancreatitis Than Biliary Sphincterotomy Alone

Abstract: In SOD patients, post-ERCP pancreatitis rates remain high, but have improved with the addition of combined pancreaticobiliary sphincter therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(91 citation statements)
references
References 15 publications
3
84
1
3
Order By: Relevance
“…Since these agents require continuous and prolonged IV infusion, they are not suited for same-day outpatient ERCP [34] . Several prospective randomized studies have shown that pancreatic stents have a beneficial role for prevention of pancreatitis in high-risk patients, including biliary and pancreatic sphincterotomy for SOD [40][41][42] , biliary balloon dilation for stone [43] and precut biliary sphincterotomy [21] . Although pancreatic stenting is …”
Section: Discussionmentioning
confidence: 99%
“…Since these agents require continuous and prolonged IV infusion, they are not suited for same-day outpatient ERCP [34] . Several prospective randomized studies have shown that pancreatic stents have a beneficial role for prevention of pancreatitis in high-risk patients, including biliary and pancreatic sphincterotomy for SOD [40][41][42] , biliary balloon dilation for stone [43] and precut biliary sphincterotomy [21] . Although pancreatic stenting is …”
Section: Discussionmentioning
confidence: 99%
“…Complications of pre-cut sphincterotomy may also vary with the indication for the procedure; in a multicenter study in which a pancreatic stent was seldom placed, precut papillotomy was associated with a higher overall rate of pancreatitis (15.3%); but, when performed for SOD, the rate was 35.3% (25% severe) compared with 11.3% (2% severe) for other indications (P = 0.01) [38] . In contrast, a subsequent study showed that needle-knife papillotomy over a pancreatic stent placed during the early stages of the procedure was shown to be substantially safer than conventional pull-type sphincterotomy without a pancreatic stent in patients with SOD [18] . Overall, the data thus suggest that traditional methods of pre-cut papillotomy are potentially injurious to the pancreas, albeit effective in experienced hands and probably safer than a protracted effort at cannulation.…”
Section: Endoscopic Sphincterotomy (Es)mentioning
confidence: 93%
“…Pancreatic stents generally should be left in place for a minimum of 2-3 d but should be removed endoscopically (repeat pancreatography usually not required) within 2-3 wk from a normal duct if spontaneous passage is not documented by a plain abdominal radiograph. Use of such prophylactic pancreatic stents in large referral centers have shown a significant reduction in rates of PEP including severe cases (Table 1) [15][16][17][18][19][20][21][22][23] .…”
Section: H Ow T O Ove R C O M E C a N Nu L A T I O N T R A U M A ? S mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most likely mechanisms is impaired drainage from the pancreatic duct caused by papillary edema or spasm of the sphincter of Oddi after ERCP procedures (10)(11)(12)(13)(14)19,22,25). Another is local injury of the papilla and pancreatic duct as a result of ERCP procedures, or forceful and repetitive contrast injections causing local inflammation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)26). This may lead to premature intracellular activation of proteolytic enzymes, consequently causing further damage and local inflammation as indicated by increased levels of cytokines, and possible initiation of a systemic inflammatory response with multi-organ involvement (1,10,11,13).…”
Section: Mechanisms Of Post-ercp Pancreatitismentioning
confidence: 99%